YEATS Domain—A Histone Acylation Reader in Health and Disease. Issue 13 (30th June 2017) - Zhao, Dan; Li, Yuanyuan; Xiong, Xiaozhe; Chen, Zhonglei; Li, Haitao
Abstract: Histone post-translational modifications (PTMs) carry an epigenetic layer of message to regulate diverse cellular processes at the chromatin level. Many of these PTMs are selectively recognized by dedicated effector proteins for normal cell growth and development, while dysregulation of these recognition events is often implicated in human diseases, notably cancer. Thus, it is fundamentally important to elucidate the regulatory mechanism(s) underlying the readout of PTMs on histones. The Y af9, E NL, A F9, T af14, S as5 (YEATS) domain is an emerging reader module that selectively recognizes histone lysine acylation with a preference for crotonylation over acetylation. In the review, we discuss the recognition of histone acylations by the YEATS domain and the biological significance of this readout from multiple perspectives. Graphical Abstract: Highlights: YEATS reads a repertoire of histone acylations with a preference for crotonylation. YEATS couples histone acylation readout to active transcription. An aromatic-π interaction contributes to crotonylation preference by YEATS. Dysfunction of YEATS domain is linked to multiple human diseases.